Морфологические данные о функциональной активности брыжеечных лимфатических узлов у макака резуса (Macacus rhesus Audeb.) - Одинцова, Л.А. (Вестник зоологии, 1972)
The structure of the lymphoid nodules of the young monkeys (Makakus rhesus 2—3 years old) testifies to their functional activity. Lymphoid follicles reach 240—260 µm in diameter. They protrude over the nodule surface and penetrate into it. On account of this the border between the cortex and medulla disappears. The lymph sinuses are filled to capacity with mature lymphocytes. The lymphoid nodule division results in an increase of the medullary substance area. The visceral blood vessels are large in diameter, the diameter of veins being 5—6 times as large as that of the corresponding arteries. The postcapillary venules, 18—24 microns in diameter, border the lymphoid follicles and are located along the lymph sinuses. The endothelium, basal membrane and perivascular argyrophfl case of the blood vessels are a substrate separating lymph from blood in the lymphoid nodule as the walls of the sinuses formed by the lymphoid tissue have no special cell lining.